Analysis of characteristics using wavelet transform for simultaneous faults in electrical power system - Pothisarn, C.; Ngaopitakkul, A. (My University, 2012)
This paper presents an analysis of characteristics for simultaneous fault signals in a 500-kV electrical power transmission system using wavelet transform. Such fault signals can occur in the transmission system, and have an effect to the operation of distance relays installed in the system. The fault analysis is performed using PSCAD/EMTDC. The Discrete Wavelet Transform (DWT) is used in order to detect the high frequency components. In addition, characteristics of fault current at various fault inception angles, fault locations and faulty phases are detailed. It has been found that when applying the previous decision algorithm give a wrong conclusion of fault types and fault location. © 2012 IEEE.
Keywords: Discrete Wavelet Transform; Power System Protection; PSCAD/EMTDC; Simultaneous Fault